2019
DOI: 10.1098/rsif.2019.0425
|View full text |Cite
|
Sign up to set email alerts
|

How eyelashes can protect the eye through inhibiting ocular water evaporation: a chemical engineering perspective

Abstract: Bionics is a fascinating subject that has inspired many inventions through learning from biological structures and functions. In this work, a coupled multi-physics model has been developed to characterize ocular water evaporation with realistic eyelash structures taken into account. From a chemical engineering perspective, the protective function of human eyelashes in terms of evaporation inhibition has been rationally revealed. Systematic investigations were carried out to elucidate the effects of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Consequently, our study documented a notably substantial increase in both curvature and arc, suggesting that these enhancements serve to improve not just the aesthetic appearance but also the functional efficacy of the eyelashes. 5 This correlation underscores the dual benefit of our product, accentuating the lashes' protective role against environmental elements while simultaneously enhancing their visual appeal.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Consequently, our study documented a notably substantial increase in both curvature and arc, suggesting that these enhancements serve to improve not just the aesthetic appearance but also the functional efficacy of the eyelashes. 5 This correlation underscores the dual benefit of our product, accentuating the lashes' protective role against environmental elements while simultaneously enhancing their visual appeal.…”
Section: Discussionmentioning
confidence: 87%
“…An in vitro study on the aerodynamics of eyelash structure has shown their essential role in eye protection. Utilizing a mammalian eye model in a wind tunnel simulation to assess airflow dynamics, researchers identified that the ideal eyelash length is one‐third of the eye's width—a measurement significantly reducing tear evaporation and deposition of foreign particles 5,15 . This optimal length, determined by biomechanical efficiency, suggests that while longer lashes might be aesthetically favored, they could impede their protective function if they exceed this proportional threshold.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another important function deserving further investigation is the inhibition of ocular water evaporation since a moist ocular surface is critical for the health of eyes [14]. The answer might seem simple: Those thick hairs on the end of our eyelids simply exist to block intruding particles from landing on our eyeballs.…”
Section: Longer Isn't Bettermentioning
confidence: 99%